THE EFFECT OF WORK MOTIVATION AND DISCIPLINE ON THE PERFORMANCE OF STATE VOCATIONAL SCHOOL TEACHERS IN NOEMUTI SUB-DISTRICT, NORTH CENTRAL TIMOR REGENCY - Ferdinandus Metkono (Academic Journal of Educational Sciences, 2022)
The purpose of this study was to determine the effect of work motivation and work discipline on the performance of State Vocational High School teachers in Noemuti District either partially or simultaneously. The subjects in this study were 51 teachers of State Vocational High Schools in Noemuti District, Timor Tengah Utara Regency. The data analysis technique used multiple linear regression analysis and classical assumption test. The method used is descriptive quantitative. Collecting data using primary and secondary data, as well as statistical tests including multiple linear regression equations, correlation coefficient tests, determination tests and hypothesis testing. The results showed that motivation (X1) and work discipline (X2) had a positive effect on teacher performance (Y) with multiple regression equations for the hypothesis that the effect of motivation and work discipline on teacher performance was a positive sign (+) indicating the relationship between the independent variable and the dependent variable was running. one-way, meaning that every increase in one variable level will be followed by an increase in another variable, so that the higher the motivation and work discipline, the higher the teacher's performance. The correlation coefficient value is 0.873. The correlation value is in the range between 0.800-0.999 which is in the Very Strong category. This value indicates that there is an influence of the variable Motivation (X1) and Work Discipline (X2) on Teacher Performance (Y). From the results of the calculation of the coefficient of determination (R Square/r2) of 0.762 or the percentage is 76.20%, while 23.80% is influenced by other factors not examined in this study. Testing the hypothesis then obtained the value of Fcount > Ftable with a value of 76.760 > 3.19, and a significance of 0.001 <0.05, thus H0 is rejected and H3 is accepted. Then the motivation variable and the work discipline variable simultaneously or together have an effect on the performance of State Vocational High School teachers in Noemuti District, North Central Timor Regency. The results of this study support the proposed hypothesis, and it is concluded that work motivation has a positive effect on teacher performance, work discipline has a positive effect on work performance and motivation and work discipline together has a positive effect on the performance of State Vocational School teachers in Noemuti District.